URGENSI EVALUASI KURIKULUM PEMBELAJARAN BAHASA ARAB DI LEMBAGA PENDIDIKAN - Munir, Muhammad Syahrul (Jurnal al Hikmah, 2018)
Any program, activity or something else planned always ends with an evaluation. The evaluation is intended to review whether a program / activity has been in accordance with the plan or not. From the evaluation activities will be known things that have / will be achieved already meet the criteria specified. Based on the results of the evaluation is then taken the decision whether the program will be forwarded or revised / even replaced entirely.Arabic learning curriculum development activities will not be separated from the evaluation element, because evaluation is one of the most important components that can not be ignored. In many ways, the assessment component is instrumental in supporting the successful development of Arabic learning curriculum, as we know, the developed curriculum is still theoretical and abstract plans. With the evaluation, we will get an idea of the success of the Arabic learning curriculum that is being / has been developed in schools. From evaluational activities will be known advantages, weaknesses and shortcomings.